2003
DOI: 10.1089/105072503322021142
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neck Ultrasonography in the Follow-Up of Children Operated on for Thyroid Papillary Cancer

Abstract: The aim of this study was to evaluate the role of neck ultrasonography compared to (131)I whole-body scan (WBS) and circulating thyroglobulin (Tg) measurement after thyroid hormone withdrawal in the follow-up of children with thyroid papillary cancer, who had previously undergone total thyroidectomy for the diagnosis of neck lymph node metastases (LNM). Forty-five children were examined. Neck ultrasonography and diagnostic WBS were conclusive about the presence or absence of LNM in 35 patients. Diagnostic WBS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 42 publications
0
66
0
3
Order By: Relevance
“…Ultrasonography has been proven to be the most efficient first-line method for the diagnosis of thyroid diseases with advantages of non-invasiveness, real-time scanning, easy performance, and wide availability. Meanwhile, it is also a mean of assessing the degree of involvement of surrounding soft tissues as well as the area involved (9,(14)(15)(16) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasonography has been proven to be the most efficient first-line method for the diagnosis of thyroid diseases with advantages of non-invasiveness, real-time scanning, easy performance, and wide availability. Meanwhile, it is also a mean of assessing the degree of involvement of surrounding soft tissues as well as the area involved (9,(14)(15)(16) …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that preexisting Hashimoto's thyroiditis is a wellrecognized risk factor for the development of PTL, and the average incidence of Hashimoto's thyroiditis in patients with PTL is 80%, ranging from 30-100% in previous studies (12,14). There is also evidence that large cell lymphoma probably evolves from persistent low-grade MALT malignant lymphoma, suggesting a morphological progression from chronic lymphocytic thyroiditis to lowgrade MALT lymphoma, and subsequently, to highgrade large-cell lymphoma (42).…”
mentioning
confidence: 99%
“…For lymph node scanning on the 2 sides of the neck and collarbone, we referred to Antonelli et al (2003) criteria.…”
Section: Thyroid Ultrasound Scanningmentioning
confidence: 99%
“…Thyroid volume was calculated by the ellipsoid formula, as previously described (14,16,17). The presence of hypoechoic and dyshomogeneous echogenicity was arbitrarily rated at three levels (0 ¼ normal echogenicity; 1 ¼ slight hypoechoic and dyshomogeneous; 2 ¼ severely hypoechoic and dyshomogeneous) to evaluate structural abnormalities of thyroid tissue associated with thyroid autoimmunity (18,19).…”
Section: Ultrasonography Of the Neck And Fnamentioning
confidence: 99%